Brown adipose tissue activation is not related to hypermetabolism in emphysematous chronic obstructive pulmonary disease patients. Issue 2 (15th February 2022) - Sanders, Karin J.C.; Wierts, Roel; van Marken Lichtenbelt, Wouter D.; de Vos‐Geelen, Judith; Plasqui, Guy; Kelders, Marco C.J.M.; Schrauwen‐Hinderling, Vera B.; Bucerius, Jan; Dingemans, Anne‐Marie C.; Mottaghy, Felix M.; Schols, Annemie M.W.J.
Abstract: Background: Brown adipose tissue (BAT) has been primarily researched as a potential target for mitigating obesity. However, the physiological significance of BAT in relation to cachexia remains poorly understood. The objective of this study was to investigate the putative contribution of BAT on different components of energy metabolism in emphysematous chronic obstructive pulmonary disease (COPD) patients. Methods: Twenty COPD patients (mean ± SD age 62 ± 6, 50% female, median [range] BMI 22.4 [15.1–32.5] kg/m 2 and 85% low FFMI) were studied. Basal metabolic rate (BMR) was assessed by ventilated hood, total daily energy expenditure (TDEE) by doubly labelled water and physical activity by triaxial accelerometry. BMR was adjusted for fat‐free mass (FFM) as assessed by deuterium dilution. Analysis of BAT and WAT was conducted in a subset of ten patients and six age‐matched, gender‐matched and BMI‐matched healthy controls. BAT glucose uptake was assessed by means of cold‐stimulated integrated [18F]FDG positron‐emission tomography and magnetic resonance imaging. WAT was collected from subcutaneous abdominal biopsies to analyse metabolic and inflammatory gene expression levels. Lung function was assessed by spirometry and body plethysmography and systemic inflammation by high sensitivity C‐reactive protein. Results: Mean TDEE was 2209 ± 394 kcal/day, and mean BMR was 1449 ± 214 kcal/day corresponding to 120% of predicted. FFM‐adjusted BMR did not correlate with lung function or C‐reactive protein. Upon cooling, energy expenditure increased, resulting in a non‐shivering thermogenesis of (median [range]) 20.1% [3.3–41.3] in patients and controls. Mean BAT glucose uptake was comparable between COPD and controls (1.5 [0.1–6.2] vs. 1.1 [0.7–3.9]). In addition, no correlation was found between BMR adjusted for FFM and BAT activity or between cold‐induced non‐shivering energy expenditure and BAT activity. Gene expression levels of the brown adipocyte or beige markers were also comparable between the groups. No (serious) adverse events were reported. Conclusions: Although COPD patients were hypermetabolic at rest, no correlation was found between BMR or TDEE and BAT activity. Furthermore, both BAT activity and gene expression levels of the brown adipocyte or beige markers were comparable between COPD patients and controls.